1995
DOI: 10.1063/1.114890
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a single photoluminescence peak from a single quantum dot

Abstract: We observed a very sharp photoluminescence peak from a single GaAs/AlGaAs quantum dot structure by using a microphotoluminescence measurement technique. The spectral linewidth was more suppressed by decreasing the excitation laser power, which is mainly due to reduction of the filling effect of quantized energy levels. The minimal spectral linewidth with low excitation laser power was 0.9 meV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…4 As quantum dots of diameter 30 nm using an sp 3 d 5 s* tight binding model. It has been demonstrated that under the assumption of no alloy clustering, the disorder-induced contribution to the broadening is small (less than 0.35 meV) compared to the empirically measured total linewidth broadening and sensitive to the applied boundary conditions, so that care must be taken to ensure proper convergence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 As quantum dots of diameter 30 nm using an sp 3 d 5 s* tight binding model. It has been demonstrated that under the assumption of no alloy clustering, the disorder-induced contribution to the broadening is small (less than 0.35 meV) compared to the empirically measured total linewidth broadening and sensitive to the applied boundary conditions, so that care must be taken to ensure proper convergence.…”
Section: Discussionmentioning
confidence: 99%
“…4 As QD of diameter 30 nm and height 5.4 nm containing roughly 2 × 10 5 atoms embedded in a finite GaAs box, which is meant to approximate an infinite one. This particular model was selected for comparison with previously published experimental results [2,3].…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that sharp luminescence from a QD can be observed under very weak excitation which creates only one electron-hole pair existing in a QD. 24,25 At higher excitation, more carriers are created in and in the vicinity of the QD, leading not only to band filling but also affecting the recombination lifetime in a QD. Since the linewidth correlates with the lifetime, we believe that this might be the cause of the spectrum broadening.…”
Section: Tsr-qds Formation and Optical Propertiesmentioning
confidence: 99%